Ring Opening Metathesis Polymerization Chap. 2 - Lyapkov A. A. Aleksey Alekseevich; Kiselev S. A. Stanislav Andreevich; Bozhenkova G. S. Galina Sergeevna; Kukurina O. S. Olga Sergeevna; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen